Eco-Theology in Indonesian Islam: Ideas on Stewardship among Muhammadiyah Members - Wijsen, Frans; Anshori, Ahmad Afnan (Journal of Government and Civil Society, 2023)
In response to environmental degradation, Muslims worldwide have been developing Green Islam and Eco- Theology. This article focuses on Indonesia, particularly on Muhammadiyah members. The authors advocate an empirical approach, based on an analysis of the beliefs of Muslims rather than on the source texts of Islam. Terms frequently used by Muslims to refer to the relationship between humans and nature is “steward” and “stewardship”. By conducting interviews, the authors aim to get a deeper insight into how these terms are used in constructing Green Islam. Interviewees say on the one hand that “all creatures are the same”, on the other hand, that humans act “as stewards, as leaders” of nature. This ambiguity raises a dilemma for Eco-Theology in Indonesian Islam: between deep ecology and eco-modernity. The interviewees, however, also see a need to go beyond this dichotomy, by moderation and balancing, or the Middle Path. The Middle Path is a life orientation that promotes “harmony between humankind, the rest of nature and the Transcendent.” Menanggapi degradasi lingkungan, umat Islam di seluruh dunia telah mengembangkan Islamdan Eco-Theology. Artikel ini berfokus pada Indonesia, khususnya pada anggota Muhammadiyah. Para penulis menganjurkan pendekatan empiris, berdasarkan analisis keyakinan Muslim daripada pada teks sumber Islam. Istilah yang sering digunakan oleh umat Islam untuk merujuk pada hubungan antara manusia dan alam adalah “penatalayanan” dan “penatalayanan”. Dengan melakukan wawancara, penulis bertujuan untuk mendapatkan wawasan yang lebih dalam tentang bagaimana istilah-istilah ini digunakan dalam membangun Islam Hijau. Orang yang diwawancarai mengatakan di satu sisi bahwa “semua makhluk adalah sama”, di sisi lain bahwa manusia bertindak “sebagai pelayan, sebagai pemimpin” alam. Ambiguitas ini menimbulkan dilema bagi eko-teologi dalam Islam Indonesia: antara ekologi dalam dan eko-modernitas. Orang yang diwawancarai, bagaimanapun, juga melihat kebutuhan untuk melampaui thadalah dikotomiy, dengan moderasi dan keseimbangan, atau Jalan Tengah. Jalan Tengah adalah orientasi hidup yang mempromosikan “harmoni antara umat manusia, seluruh alam dan Transenden.”